Informality and employment vulnerability: application in sellers with subsistence work - María Osley Garzón-Duque; María Doris Cardona-Arango; Fabio León Rodríguez-Ospina; Angela María Segura-Cardona (Revista de Saúde Pública, 2017)
ABSTRACT OBJECTIVE To describe the origin, evolution, and application of the concept of employment vulnerability in workers who subsist on street sales. METHODS We have carried out an analysis of the literature in database in Spanish, Portuguese, and English, without restriction by country. This is a review of the gray literature of government reports, articles, and documents from Latin America and the Caribbean. We have analyzed information on the informal economy, social-employment vulnerability, and subsistence workers. RESULTS AND CONCLUSIONS The concept of informal economy is dispersed and suggested as synonymous with employment vulnerability. As a polysemic term, it generates confusion and difficulty in identifying defined profiles of employment vulnerability in informal subsistence workers, who sell their products on the streets and sidewalks of cities. The lack of a clear concept and profile of employment vulnerability for this type of workers generates a restriction on defined actions to reduce employment vulnerability. The profiles could facilitate access to the acquisition of assets that support their structure of opportunities, facilitating and mediating in the passage from vulnerability to social mobility with opportunities. We propose as a concept of employment vulnerability for subsistence workers in the informal sector, the condition of those who must work by day to eat at night, who have little or no ownership of assets, and who have a minimum structure of opportunities to prevent, face, and resist the critical situations that occur daily, putting at risk their subsistence and that of the persons who are their responsibility, thus making the connection between social and employment vulnerability.